Royal patrons and great temple art - Dehejia, Vidya (Bombay Marg Publications, 1988)
On the art and architecture of selected Hindu temples in India; contributed articles.
Includes bibliographies.
Keywords: Art, Hindu; Architecture, Hindu; Art patronage -- India; Temples, Hindu